214k views
2 votes
0= (x-1)^2 -4 and and show explanation please

2 Answers

0 votes
x=-1. x=3 hopefully this is correct
User Jmcneirney
by
5.7k points
4 votes

Answer:

x=-1, x=3

Explanation:

to solve by factoring:

1. swap the sides:

0=(x-1)^2-4

2. expand the expression:

(x-1)^2-4=0

3. rewrite and calculate:

x^2-2x+1-4=0

4. factor

x^2+x-3x-3=0

5. Factor... again

x(x+1)-3(x+1)=0

6. separate

(x+1) (x-3)=0

7. solve

x+1=0, x-3=0

8. and you end up with 2 solutions

x=-1, x=3

User Nashuald
by
6.1k points